The geology, geochemistry and metallogeny of the felsic rocks of the bushveld complex, North of Bronkhorstspruit, South Africa - Bailie, Russell Hope (My University, 2016)
The felsic rocks ofthe Bushveld Complex are host to abundant, small polymetallic mineralisation. The study involved mapping and metallogenic characterisation of an area north of Bronkhoratspruit, in the acid phase of the Bushveld Complex. The upper Rooiberg Group shows an evolution from rhyodacites of the Kwaggasnek Formation to rhyolites of the Schrikkloof'Formarion. The Rooiberg Group formed from the same magma that formed the underlying granophyres. The granites represent further fractionation of the same parental magma, evolving from grey hornblende-rich granites at the base of the sheet to red biotite-rich granites at the top. Mineralisation is derived from highly fractionated granites that evolved to water saturation. Structural controls also influenced hydrothermal fluid flow. The mineralisation progresses from a magmatic Sn assemblage through a Cu-Pb-Zn assemblage to a late meteoric Fe-U-F assemblage superimposed on earlier assemblages. Progressive fluid mixing from magmatic to meteoric characterised the development of the paragenetic sequence.
A dissertation submitted to the Faculty of Science, University (If the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 1997